COMMONALITY OF UZBEKISTAN AND TURKISH LANGUAGES - Oʻktamov Tohirjon (Web of Journals Publishing, 2025)
This article provides information about the process of formation of the Uzbek language, the period and stages of development, and the role of languages of other systems in the formation of the Uzbek literary language.
Keywords: Altai, Orkhon-Enasay,